Aquaporins as Membrane Proteins: The Current Status - Irena Roterman; Katarzyna Stapor; Dawid Dułak; Grzegorz Szoniec; Leszek Konieczny (Frontiers in Bioscience-Scholar)
Background: The ambient conditions that ensure the expected protein folding activity are important in directing the protein folding process. Water favors the formation of a centrally located hydrophobic protein nucleus with exposed polar residues for preferable contact with polar water molecules. Different ambient conditions are created by the hydrophobic cell membrane, which also provides an environment for the activity of proteins, including channels responsible for transporting multiple molecules, the concentration of which is controlled as part of homeostasis. Aquaporins are transmembrane proteins responsible for primarily transporting water and low-molecular-weight compounds. Methods: The fuzzy oil drop (FOD) model was applied in its modified form, FOD-M, for the analysis. The FOD model allows quantitative assessment of protein structure adaptation to external conditions, ensuring its biological activity. Results: The aquaporins studied in this work revealed adaptations for stabilizing hydrophobic environments and transporting polar molecules. Conclusions: A significant degree of similarity was demonstrated in the structure of human aquaporins using FOD-M. This model enabled a quantitative assessment of the degree of adaptation to biological function achieved through an appropriate balance between micelle-like decomposition and appropriate modification due to the specificity of the environment that ensures adequate activity.